Young suicide attempters in public places: a comprehensive study - Saraiva, Carlos Manuel Braz (2014)
Introduction The current socio-economic crisis highlighted some kind of suicidal behaviours in public places. This particular interest leads us to study these behaviours in our data. Methods Patients referred to our Suicide Research and Prevention Unit were assessed through a semi-structured interview covering both social and clinical aspects. We compared two samples of young suicide attempters (n=448): one, who performed there suicidal behaviour in public places (14.3%) and others. Statistical analysis was conducted using SPSS 22. Results Concerning the first sample, we found these main differences: More males, alcohol and other substances abuse, selfpoisoning by pesticides, ritualization behaviour, ask for help before act, suicidal intention (patient opinion and doctor evaluation); and Less religious, psychotropics abuse and impulsiveness. Discussion These findings reveal a different profile between the youngs who performed suicidal behaviours in public places, from the generality of the young suicidal attempters: they are male, using more violent methods, more planning and with higher suicidal intention; despite that they ask for help before the suicidal act. Conclusions Those data appeal to Werther effect with all consequences of imitation and contagious of these kinds of behaviours. So we can speculate that there despair wasn't understood in a previous crisis, before the suicidal act.